Cytochrome P450 family member CYP96B5 hydroxylates alkanes to primary alcohols and is involved in rice leaf cuticular wax synthesis. Issue 5 (25th November 2019) - Zhang, Du; Yang, Huifang; Wang, Xiaochen; Qiu, Yijian; Tian, Lihong; Qi, Xiaoquan; Qu, Le Qing
Summary: Odd‐numbered primary alcohols are components of plant cuticular wax, but their biosynthesis remains unknown. We isolated a rice wax crystal‐sparse leaf 5 ( WSL5 ) gene using a map‐based cloning strategy. The function of WSL5 was illustrated by overexpression and knockout in rice, heterologous expression in Arabidopsis and transient expression in tobacco leaves. WSL5 is predicted to encode a cytochrome P450 family member CYP96B5. The wsl5 mutant lacked crystalloid platelets on the surface of cuticle membrane, and its cuticle membrane was thicker than that of the wild‐type. The wsl5 mutant is more tolerant to drought stress. The load of C23 –C33 alkanes increased, whereas the C29 primary alcohol reduced significantly in wsl5 mutant and WSL5 knockout transgenic plants. Overexpression of WSL5 increased the C29 primary alcohol and decreased alkanes in rice leaves. Heterologous expression of WSL5 increased the C29 primary alcohol and decreased alkanes, secondary alcohol, and ketone in Arabidopsis stem wax. Transient expression of WSL5 in tobacco leaves also increased the production C29 primary alcohol. WSL5 catalyzes the terminal hydroxylation of alkanes, yielding odd‐numbered primary alcohols, and is involved in the formation of epidermal wax crystals on rice leaf, affecting drought sensitivity.